Investigation of DC distribution network with renewables and DC load - Low, Dennis Bo Xiang (Nanyang Technological University, 2023)
The rise of digitalisation in recent years has demanded for significantly larger use of DC loads such as laptops, cell phones and data centres. There is also an expanding percentage of consumers who are turning to DC appliances and products such as solar panels and LEDs for improved home energy savings. In addition, there is a growing trend for electric vehicles of which the local government is also installing increasingly more EV chargers in public spaces to encourage the use of EV in an effort to reduce carbon emissions. Along with the increase in DC loads in the current network, there is increasing power loss due to multiple conversion stages involved. Therefore, this surge in usage of renewables and DC loads and shift in consumer needs have called for engineers to relook into the current AC electricity network. In this paper, a framework was formulated to analyse the efficiency impact of conventionally used low voltage levels of 400V in AC against 380V in DC, serving to small-scale residential complex with loads of voltage ratings 400Vac, 380Vdc, 48Vdc and 24Vdc loads, of which resulted in 8% higher efficiency in DC system. The degree of efficiency mainly draws on factors such as cable length, DC voltage levels and loads connected. Subsequently, the result of efficiency was evaluated against potential challenges such as DC protection systems and the associated costs of DC systems. The findings ultimately suggest the relatively low feasibility of transiting the current grid to DC distribution entirely, and propose for a hybrid AC/DC distribution system network.